2016
DOI: 10.1016/j.molcel.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Cyclin-Dependent Kinase Routes Carbon Fluxes to Fuel Cell Cycle Progression

Abstract: Cell division entails a sequence of processes whose specific demands for biosynthetic precursors and energy place dynamic requirements on metabolism. However, little is known about how metabolic fluxes are coordinated with the cell division cycle. Here, we examine budding yeast to show that over half of all measured metabolites change significantly through the cell division cycle. Cell cycle-dependent changes in central carbon metabolism are controlled by the cyclin-dependent kinase Cdk1, a major cell cycle re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
145
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(156 citation statements)
references
References 77 publications
(102 reference statements)
8
145
3
Order By: Relevance
“…It is possible that p21-dependent inhibition of additional or alternative CDKs (e.g., CDK1/2) is required to conserve GSH and inhibits ferroptosis through induction of a more complete cell-cycle arrest. Alternatively, p21 could potentially enhance GSH retention through effects on CDK-regulated metabolic enzymes (Ewald et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that p21-dependent inhibition of additional or alternative CDKs (e.g., CDK1/2) is required to conserve GSH and inhibits ferroptosis through induction of a more complete cell-cycle arrest. Alternatively, p21 could potentially enhance GSH retention through effects on CDK-regulated metabolic enzymes (Ewald et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…2012; Cai and Tu 2012; Ewald et al. 2016; Zhao et al. 2016) and in mammalian cells (Lim and Kaldis 2013; Kaplon, van Dam and Peeper 2015).…”
Section: Perspectives: Integrating Binary Logic With Stoichiometry Tomentioning
confidence: 99%
“…The integrative model has been validated by testing the regulation of trehalose degradation, which has been recently suggested to occur in both in vitro and in vivo experiments by Cdk1-mediated phosphorylation of the trehalase Nth1 (Ewald et al. 2016; Zhao et al. 2016).…”
Section: Perspectives: Integrating Binary Logic With Stoichiometry Tomentioning
confidence: 99%
“…For instance, Zhao, Chen, Carey, and Futcher (2016) and Ewald, Kuehne, Zamboni, and Skotheim (2016) note that the CDC and metabolism have many regulatory genes in common. Additionally, understanding yeast oscillations and regulation of metabolism is important in the efficient management of bioprocesses (Beuse, Kopmann, Diekmann, & Thoma, 1999;Uchiyama, Morimoto, Yokoyama, & Shioya, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed biochemical models of the growth and division processes within a single fission yeast's cell cycle, including checkpoint controls, were considered in Novak, Csikasz-Nagy, Gyorffy, Chen, and Tyson (1998). Recently, Zhao et al (2016) and Ewald et al (2016) observed that the use of internal carbohydrates is regulated by CDK activity. CDKs have long been known to be primary regulatory agents in the cell cycle.…”
Section: Introductionmentioning
confidence: 99%